2013
DOI: 10.1155/2013/975251
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Ectopic Pregnancies in Eastern Saudi Arabia

Abstract: Background. The objective of this study was to estimate trends in ectopic pregnancies (EP) in a tertiary care center of Eastern Saudi Arabia. Method. Information about patients with ectopic pregnancies who had been admitted to King Fahd Hospital of the University, AlKhobar, between January 2000 and 31 December 2011 was collected from a computerized hospital registry. Age-specific ectopic pregnancy incidence was calculated. The data was analyzed using SPSS (Statistical Package for the Social Sciences), version … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…There was a significant difference in the findings between our study and the findings of a study by Bouyer et al [4] . Al-Turki et al [5] also showed that majority of the patients (61.1%) were below the age of 30 yrs. Hamura et al [6] showed a majority of the cases (95%) were aged >25 yrs.…”
Section: Discussionmentioning
confidence: 91%
“…There was a significant difference in the findings between our study and the findings of a study by Bouyer et al [4] . Al-Turki et al [5] also showed that majority of the patients (61.1%) were below the age of 30 yrs. Hamura et al [6] showed a majority of the cases (95%) were aged >25 yrs.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, a study conducted at the Royal Commission Medical Center (RCMC), Yanbu Industrial City, estimated that the rate of ectopic pregnancy was 0.58% at the center [ 4 ]. Further, a study conducted at King Fahd University Hospital, Al Khobar, to estimate the prevalence of ectopic pregnancy between January 1, 2000, and December 31, 2011, established that out of 24,098 deliveries, 274 (1.19%) were diagnosed as ectopic pregnancies [ 5 ]. The study concluded that the majority of cases (61.1%) involved women under the age of 30.…”
Section: Introductionmentioning
confidence: 99%
“…It is an important cause of maternal morbidity and mortality. 8 The incidence of ectopic pregnancy varies greatly throughout the world and incidence is increasing worldwide. 9 The reported incidence of ectopic pregnancy was 3-4% of all pregnancies throughout the world.…”
Section: Discussionmentioning
confidence: 99%